On Consensus of Multiple High-Order Uncertain Systems Based on Distributed Backstepping Framework. (1st August 2014) - Huang, Jie; Chen, Chen; Fang, Hao; Chen, Jie; Dou, Lihua
This paper focuses on the consensus problem of multiple high-order systems with uncertainties. Since it is difficult to use matrix theory approaches to design consensus controllers for a class of multiple high-order uncertain nonlinear systems, in this paper a set of consensus control laws are proposed by employing adaptive control theory and a backstepping technique. The distributed virtual control functions of the multi-agent systems are elaborately constructed by only using their local information in the recursive controller design procedure. Furthermore, the asymptotic stability of the overall interconnected system is proved relying on the Lyapunov stability analysis method. Finally, simulations are provided to verify the effectiveness of the control algorithms.